Direct Growth of Ge1−xSnx Films on Si Using a Cold-Wall Ultra-High Vacuum Chemical-Vapor-Deposition System - Mosleh, Aboozar; Alher, Murtadha A.; Cousar, Larry C.; Du, Wei; Ghetmiri, Seyed Amir; Pham, Thach; Grant, Joshua M.; Sun, Greg; Soref, Richard A.; Li, Baohua; Naseem, Hameed A.; Yu, Shui-Qing (Frontiers in Materials, 2015)
Germanium tin alloys were grown directly on Si substrate at low temperatures using a cold-wall ultra-high vacuum chemical vapor deposition system. Epitaxial growth was achieved by adopting commercial gas precursors of germane and stannic chloride without any carrier gases. The X-ray diffraction analysis showed the incorporation of Sn and that the Ge1-xSnx films are fully epitaxial and strain relaxed. Tin incorporation in the Ge matrix was found to vary from 1% to 7%. The scanning electron microscopy images and energy dispersive X-ray spectra maps show uniform Sn incorporation and continuous film growth. Investigation of deposition parameters shows that at high flow rates of stannic chloride the films were etched due to the production of HCl. The photoluminescence study shows the reduction of bandgap from 0.8 eV to 0.55 eV as a result of Sn incorporation.